Réponses

  • Utilisateur Brainly
2013-04-18T13:07:33+02:00

φ=(1+√5)/2 donc φ²=((1+√5)/2)²=(1+5+2√5)/4=(6+2√5)/4=(3+√5)/2

 

φ+1=(1+√5)/2+1 =(1+2+√5)/2=(3+√5)/2

 

donc φ²=φ+1 donc φ²-φ-1=0

 

de plus φ-1=(1+√5)/2-1=(1-2+√5)/2=(-1+√5)/2

donc 1/(φ-1)=2/(-1+√5)=(2(-1-√5))/(1-5)=(-2-2√5)/(-4)=(1+√5)/2

 

donc 1/(φ-1)=φ

Meilleure réponse !
2013-04-18T13:21:59+02:00

Voila un e réponse jespere que je tauré aidé

 

De plusφ=(1+√5)/2 donc φ²=((1+√5)/2)²=(1+5+2√5)/4=(6+2√5)/4=(3+√5)/2

Doncφ+1=(1+√5)/2+1 =(1+2+√5)/2=(3+√5)/2

Donc φ²=φ+1 donc φ²-φ-1=0

 

 

De plus φ-1=(1+√5)/2-1=(1-2+√5)/2=(-1+√5)/2

Donc 1/(φ-1)=2/(-1+√5)=(2(-1-√5))/(1-5)=(-2-2√5)/(-4)=(1+√5)/2

Donc 1/(φ-1)=φ